The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1413-785220182605196038
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Negative-Pressure Wound Therapy in Revision Total Hip Arthroplasty Due to Infection

Abstract: ObjectiveTo present our institution's experience with negative-pressure wound therapy (NPWT) as an adjuvant in wound healing of patients who have undergone revision total hip arthroplasty (THA) due to septic loosening in the presence of active fistula.MethodsWe prospectively assessed patients presenting with THA infection, associated with the presence of fistula, treated with a PICO® device for NPWT, in combination with the standard treatment for prosthesis infection in our institution. Resolution of the infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…Despite that, a higher incidence of wound problems or haematoma formation in our population was not confirmed. Wound healing problems are more frequent in RHA 21 . Our results stay in line with Ashraf et al, who showed that in RHA suction drainage did not protect against wound oozing and haematoma formation 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Despite that, a higher incidence of wound problems or haematoma formation in our population was not confirmed. Wound healing problems are more frequent in RHA 21 . Our results stay in line with Ashraf et al, who showed that in RHA suction drainage did not protect against wound oozing and haematoma formation 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Despite that, a higher incidence of wound problems or haematoma formation in our population was not con rmed. Wound healing problems are more frequent in RHA [20].…”
Section: Discussionmentioning
confidence: 98%
“…Another study focused on the interest of CiNPWT after post-SSI revision of orthopedic implants [26] for total hip arthroplasty (THA) due to septic loosening in the presence of active fistula. They were treated with a PICO® device for NPWT, in combination with the standard treatment for prosthesis infection.…”
Section: Closed Incision Negative Pressure Therapymentioning
confidence: 99%